2018
DOI: 10.1111/aas.13305
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal betamethasone for cancer pain: A study of its analgesic efficacy and safety

Abstract: Background A preliminary study has shown effective cancer pain relief by intrathecal betamethasone (ITB). However, further evidence is needed to support this new approach. Methods Cancer patients with opioid‐resistant pain received lumbar intrathecal administration of betamethasone 2 or 3 mg once a week for 28 days. Immediate and short‐term analgesia (using a percentage pain reduction scale and a numerical rating scale, NRS) and long‐term analgesia (using NRS) were assessed. Patients were classified into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In a recent article [12], a monocentric retrospective study involving 104 patients showed a significant improvement in pain by injecting intrathecally 2-3 mg of betamethasone once a week for 1 month in cancer patients with opioid-refractory pain. This improvement was present and significant only in patients with secondary spinal lesions.…”
Section: Intrathecal Betamethasonementioning
confidence: 99%
“…In a recent article [12], a monocentric retrospective study involving 104 patients showed a significant improvement in pain by injecting intrathecally 2-3 mg of betamethasone once a week for 1 month in cancer patients with opioid-refractory pain. This improvement was present and significant only in patients with secondary spinal lesions.…”
Section: Intrathecal Betamethasonementioning
confidence: 99%
“…Additionally, group D4 had a considerably longer duration to the first rescue analgesic dose (min) than the other two groups. Taguchi et al (12) revealed that three patients with unremitting cancer pain had their pain score successfully reduced by intrathecal injection of betamethasone. According to a different study, laparoscopic cholecystectomy with dexamethasone (4 mg) lowers post-operative pain scores and morphine usage (13) .…”
Section: Discussionmentioning
confidence: 99%